Upaya Meningkatkan Sistem Kekebalan Tubuh Anak Usia Sekolah di Masa Pandemi COVID-19 - Salim, Hotimah Masdan; Bintarti, Tri Wahyuni; Fitriyah, Fifi Khoirul; Alam, Ilham Putra; Muhammada, Davida Sajid; Nisaussholihah, Nadia (University of Merdeka Malang, 2021)
COVID-19 is a SARS virus infection that has spread throughout the world including in Indonesia. The existence of this pandemic has a significant impact on all countries, such as health, economy, education, and all supporting sectors of a country. In Indonesia itself adapting the New Normal to deal with this global pandemic. New Normal is associated with new habit changes that also impact the health level of children. So, the purpose of community service (PKM) is to provide education as an effort to increase the child's immune system in the face of the COVID-19 pandemic. This PKM is implemented at the Baca Rumah Kita Foundation in the Mejoyo Tenggilis sub-district. This PKM is carried out by presenting counseling to school-age children with interactive methods and games as well as health checks as screening and providing supplements to improve the child's immune system. Based on the PKM results, it was found that the children were enthusiastic about this activity. From the results of health screening, participants aged 5-10 years were 84.21%. With a nutritional status of 47.37% less, 15.79% less nutrition, 26.32% good nutrition, and 10.53% over nutrition. Based on the results of this screening, it can be used as a measure that the growth and development of children in this region needs special attention, especially during the current pandemic.DOI:Â https://doi.org/10.26905/abdimas.v6i2.5001